2018
DOI: 10.3390/cancers10030085
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pattern Recognition Receptors in KSHV Infection

Abstract: Kaposi’s sarcoma-associated herpesvirus or Human herpesvirus-8 (KSHV/HHV-8), an oncogenic human herpesvirus and the leading cause of cancer in HIV-infected individuals, is a major public health concern with recurring reports of epidemics on a global level. The early detection of KSHV virus and subsequent activation of the antiviral immune response by the host’s immune system are crucial to prevent KSHV infection. The host’s immune system is an evolutionary conserved system that provides the most important line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 199 publications
0
21
0
Order By: Relevance
“…During KSHV latent infection, most of the viral genome is suppressed through DNA methylation, repressive histone modifications and other regulatory mechanisms which negatively regulate gene expression ( Pantry and Medveczky, 2009 ; Gunther and Grundhoff, 2010 ; Lu et al, 2010 ; Toth et al, 2010 ; Purushothaman et al, 2015 ). Changes in the host cell microenvironment could reactivate the virus from latency to the lytic cycle, wherein the inhibitory epigenetic marks are replaced by active ones to allow for transcription of viral lytic genes ( Ye, 2017 ; Uppal et al, 2018 ). Three recent studies revealed that the KSHV life cycle was affected by RNA N 6 -adenosine methylation epigenetic modification ( Ye et al, 2017 ; Hesser et al, 2018 ; Tan et al, 2018 ).…”
Section: Role Of M 6 a In The Infection Of Dna Virmentioning
confidence: 99%
“…During KSHV latent infection, most of the viral genome is suppressed through DNA methylation, repressive histone modifications and other regulatory mechanisms which negatively regulate gene expression ( Pantry and Medveczky, 2009 ; Gunther and Grundhoff, 2010 ; Lu et al, 2010 ; Toth et al, 2010 ; Purushothaman et al, 2015 ). Changes in the host cell microenvironment could reactivate the virus from latency to the lytic cycle, wherein the inhibitory epigenetic marks are replaced by active ones to allow for transcription of viral lytic genes ( Ye, 2017 ; Uppal et al, 2018 ). Three recent studies revealed that the KSHV life cycle was affected by RNA N 6 -adenosine methylation epigenetic modification ( Ye et al, 2017 ; Hesser et al, 2018 ; Tan et al, 2018 ).…”
Section: Role Of M 6 a In The Infection Of Dna Virmentioning
confidence: 99%
“…Due to their activation during herpesvirus infection and broadly acting signaling cascades, we considered that innate immune signaling may be involved upstream of B2 SINE induction. Pattern recognition receptors, namely, the toll-like receptors 2, 3, 7, and 9, RIG-I-like receptors, and AIM2, can become activated during lytic herpesvirus infection (44)(45)(46)(47). To examine the possible upstream involvement of infection-induced innate immune signaling in the induction of B2 SINE transcription, we quantified B2 SINE levels in primary BMDMs derived from WT B6 mice versus mice lacking several canonical innate immune signaling pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their activation during herpesvirus infection and broadly acting signaling cascades, we considered that innate immune signaling may be involved upstream of B2 SINE induction. Pattern recognition receptors, namely the toll-like receptors 2, 3, 7, and 9, RIG-I-like receptors, and AIM2, can become activated during lytic herpesvirus infection [4346]. To examine the possible upstream involvement of infection-induced innate immune signaling in the induction of B2 SINE transcription, we quantified B2 SINE levels in primary BMDMs derived from WT B6 mice versus mice lacking several canonical innate immune signaling pathways.…”
Section: Resultsmentioning
confidence: 99%